Emerging public debt challenges in sub-Saharan Africa - Maureen Were (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Sub-Saharan Africa (SSA)'s public debt burden remains a challenge to development. Key drivers of public debt include large-scale financing of infrastructure development, adverse impact of multiple shocks including COVID-19 pandemic, maturity mismatches, and high vulnerability to exchange rate and interest rate volatility. The tight financial conditions following interest rate hikes in advanced economies have exacerbated the debt burden and heightened debt sustainability risks. Half of the SSA low-income countries are either in debt distress or at high risk of it. Countries in debt distress include middle-income economies. Given the high cost of debt servicing and lack of fiscal space, achievement of sustainable development goals is in jeopardy. A long-term sustainable solution requires a multi-pronged approach. The G20 Common Framework for debt treatment remains limited in scope, coverage, and impact. More needs to be done including consideration for debt relief. Other strategies include access to long-term concessional finance, domestic resource mobilization, and improved efficiency in public spending and fiscal management.
Keywords: H63; H68; E60; 330; public debt; debt sustainability; sub-Saharan Africa